Reproductive life in women with celiac disease; a nationwide, population-based matched cohort study. Issue 8 (15th June 2018) - Grode, L; Bech, B H; Plana-Ripoll, O; Bliddal, M; Agerholm, I E; Humaidan, P; Ramlau-Hansen, C H
Abstract: STUDY QUESTION: How does celiac disease (CD) influence women's reproductive life, both prior to and after the diagnosis? SUMMARY ANSWER: Prior to the diagnosis of CD, an increased risk of adverse pregnancy outcomes was seen, whereas after the diagnosis, no influence on reproductive outcomes was found. WHAT IS KNOWN ALREADY: CD has been associated with several conditions influencing female reproduction and pregnancy outcomes including spontaneous abortion and stillbirth. STUDY DESIGN, SIZE, DURATION: A nationwide matched cohort study following 6319 women diagnosed with CD and 63166 comparison women and identifying reproductive events between the ages of 15 and 50 years. PARTICIPANTS/MATERIALS, SETTING, METHODS: Through linkage of several Danish national health registers, we identified all women diagnosed with CD between 1977 and 2016. We identified an age- and sex-matched comparison cohort and obtained data on reproductive outcomes for both cohorts. Adjusted stratified Cox and logistic regression models were used to estimate differences in reproductive outcomes between women with and without CD. MAIN RESULTS AND THE ROLE OF CHANCE: Comparing women with diagnosed CD with the non-CD women, the chance of pregnancy, live birth and risk of stillbirth, molar and ectopic pregnancy, spontaneous abortion and abortion due to foetal disease was the same. However, prior to being diagnosed, CD women had an excess risk of spontaneous abortion equal to 11 extra spontaneous abortions per 1000 pregnancies (adjusted odds ratio (OR) = 1.12, 95% CI: 1.03, 1.22) and 1.62 extra stillbirths per 1000 pregnancies (adjusted OR = 1.57, 95% CI: 1.05, 2.33) compared with the non-CD women. In the period 0–2 years prior to diagnosis fewer pregnancies occurred in the undiagnosed CD group, equal to 25 (95% CI: 20–31) fewer pregnancies per 1000 pregnancies compared to the non-CD group and in addition, fewer undiagnosed CD women initiated ART-treatment in this period, corresponding to 4.8 (95% CI: 0.9, 8.7) fewer per 1000 women compared to non-CD women. LIMITATIONS, REASONS FOR CAUTION: Validity of the diagnoses in the registers was not confirmed, but reporting to the registers is mandatory for all hospitals in Denmark. Not all spontaneous abortions will come to attention and be registered, whereas live- and stillbirths, ectopic and molar pregnancies and abortion due to foetal disease are unlikely not to be registered. We adjusted for several confounding factors but residual confounding cannot be ruled out. WIDER IMPLICATIONS OF THE FINDINGS: These findings suggest that undiagnosed CD can affect female reproduction and the focus should be on early detection of CD in risk groups. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by the Health Research Fund of Central Denmark Region and The Hede Nielsens Foundation, Denmark. The authors report no conflicts of interest in this work.